STUDIES OF DISEASE INCIDENCE AND SEVERITY CAUSED BY CERCOSPORA LEAF SPOT ON DIFFERENT COWPEA (Vigna unguigulata L.Walp.) VARIETIES IN YOLA, ADAMAWA STATE, NIGERIA - WILLIAMS, W. S.; NAHUNNARO, H.; CHIMBEKUJWO I.B; AHMAD, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Cercospora Leaf Spot (CLS) caused by Cercospora canscense of cowpea (Vigna unguigulata L.Walp) is a major constraint against cowpea cultivation. In the wake of rising cost of chemical control studied in Modibbo Adama University, Yola. The main objective of the study was to determine the effectiveness of neem and pawpaw leaves extract for the control of CLS disease of cowpea while the varieties used include SAMPEA-1, SAMPEA-2, SAMPEA-3, SAMPEA-4, SAMPEA-5, SAMPEA-6, SAMPEA-7, SAMPEA-8, SAMPEA-9 and SAMPEA-10. The study comprised laboratory studies, green house and field experiments. The field experiment employed a factorial experiment consisting of 20 treatments laid out in a Randomised Complete Block Design replicated three times with plant extract placed on the main plot while varieties placed on the sub-plot during 2019 and 2020 seasons. The results revealed that all the varieties were infected by cercospora leaf spot disease at varying levels. Control plants had significantly highest disease severity throughout 2019 and 2020, in 2019 at 7WAS control recorded the mean value of 24.63 followed by neem with 24.01 while the least of 18.90 was obtained from pawpaw leave extract. SAMPEA 8 had the highest disease severity of 30.29 followed by SAMPEA 9 with 29.91 while the least of 10.14 was obtained from SAMPEA 5. Therefore, adoption of neem and pawpaw leave extract as alternatives and better remedies to CLS disease control is recommended.